(untitled) (City: History, Culture, Society, 2017)
There are official and traditional names of places upon the territory of the town or the city. They have existed from the ancient times till contemporary days. The official ones have been given by the executive body, and the traditional names are describing the place by nearby locations, buildings or natural objects. Toponyms are divided into different classes and subclasses. Horonyms describe nonlinear structures (territories) and were used to call any places on the town’s area, except for streets or squares. Horonyms do not provide the information about the official administrative division of the contemporary time but were putting traditional names in use. In order to answer the question - how long this class of the city’s names lasted, one has to base on retrospective comparison of the pre-statistical source. The contemporary vocabulary of Lviv’s dialect (“Leksykon lvivskyy povazhno i na zhart”) have fixed 65 horonyms of Lviv’s area, which currently are being used by city dwellers. That was the basement of analysis by the retrospective method. This data was compared with such sources: late 19 c.-early 20 c. guidebooks and middle 19 c. maps with their accompaniment notes. The administrative units’ division of Lviv’s territory was applied in this article because during the long 19 century Lviv was a part of Austro-Hungary Empire. That’s why 4 groups of horonyms were excluded: 1. the names of the former city’s villages that are currently preserved as the city’s horonyms because those villages were absorbed into the city only during 20th century. (Today names of those former villages do not reflect the administrative units’ division); 2. village Sygnivka, which was founded only in the 20th years of 19th century on the area of the former suburb Halytskie of Lviv’s early modern period; 3. the names of villages, which surrounded town’s area, but were not under the rule of the town hall; 4. all names of objects, which were upon the area of these villages. So after the exclusion, we have 48 names (horonyms). The analysis showed that one name came into being in the late 20th century and eight other ones during its first half. Fifteen horonyms, as well, as their names were founded during the 19th century. So, that leaves us with twenty-four names, which were established during the earlier period and are being used now in the city. We need to continue research on a retrospective comparison of the named recorded in the early modern serial sources.